Spontaneous regeneration of eucalypts from seed production areas - Miolaro, Lygia Gago; Gonçalves, Antonio Natal; Mendes, João Carlos Teixeira; e Moreira, Rildo Moreira; Brune, Arno; da Silva, Paulo Henrique Müller [UNESP] (My University, 2017)
Eucalypt species are widely used around the world due to their high productivity; however there are some concerns about the invasiveness capacity of eucalypts. We assessed old seed production areas of commercial eucalypt species thought of being at risk of invasion in two places in Southeastern Brazil (Anhembi: lat: 22°28′S; long: 48°04′W; and Itatinga lat: 23°02′S; long: 48°38′W). We observed differences between places and among species. The species with the higher number of plantation stands and higher demand for seeds had more regeneration. Regeneration was recorded in only a few plots and trees and seedlings were found very close to the eucalypt stand, in sites where waste from seed harvesting is dumped. For spontaneous regeneration of eucalypts to occur there is a need for favorable environmental conditions. Such conditions may be created by human activities or natural events which suppress competition from vegetation.
Keywords: Anthropic action; Competition; Environmental conditions; Invasibility; Invasiveness; Prediction